2023
DOI: 10.1253/circrep.cr-22-0130
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Discovery of Genes in the Three Phases of Autophagy That Are Upregulated During Atrial Fibrillation

Abstract: Background: Autophagy may contribute to the maintenance of atrial fibrillation (AF), but no previous study has concurrently surveyed all 3 phases of autophagy, namely autophagosome formation, lysosome formation, and autophagosome-lysosome fusion. Here we aimed to identify disorders involving various phases of autophagy during AF. Methods and Results: We used bioinformatic techniques to analyze publicly available DNA microarray datasets from the left atrium (LA) and righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Life phenomena, such as autophagy, which is involved in aging [9][10][11], are also involved in AF onset. Using bioinformatic analysis, we also showed that autophagy was increased in the left atrium of patients with AF [12].…”
Section: Introductionmentioning
confidence: 82%
“…Life phenomena, such as autophagy, which is involved in aging [9][10][11], are also involved in AF onset. Using bioinformatic analysis, we also showed that autophagy was increased in the left atrium of patients with AF [12].…”
Section: Introductionmentioning
confidence: 82%
“… 20 Even in case of atrial fibrillation, our previous research revealed that atrial fibrillation is related to autophagy. 21 It was also elucidated that the frequency of occurrence of “mitophagy” increased significantly since 2019. When we compared the word clouds created for “1984–2018” and “2019–2023” (Figure 3A,B ), the term “mitochondria” appeared frequently until 2008, and the term “autophagy” appeared frequently since 2018.…”
Section: Discussionmentioning
confidence: 99%
“…For intergroup comparison, rank products were utilized after normalizing the intensity files. Expression change was selected when the false discovery rate (FDR) values were <0.2 [ 46 ].…”
Section: Methodsmentioning
confidence: 99%